Analisis Retorika Pada Pidato Presiden Jokowi “Bersatu Menghadapi Corona” Sebagai Himbauan Melalui Media Youtube - Faza Fat Han Fadhillah; Irwansyah Irwansyah (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
During this COVID-19 pandemic, many people were confused about how to deal with COVID-19. In dealing with this, President Joko Widodo made a virtual speech to deal with this pandemic in order to prevent the spread of the COVID-19 virus. Based on this background, this study will discuss the meaning of the rhetorical study from President Jokowi, which contains an appeal to continue to live the days according to the Covid 19 protocol. This research was conducted with a qualitative approach and used descriptive analysis methods, which provide an overview and understanding to the reader about Aristotle's rhetorical theory in the art of persuasion carried out by President Jokowi through a press release on